The Role Of Career Path Dimensions In Reducing Occupational Combustion Among Workers In Syrian Universities - علي ديب, كندة; محمد , رامي; خلوف, رنيم (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The aimed of the research is to determine the role of career path dimensions through (training, promotion, incentives) in reducing job burnout (stress, and the limited work powers of workers at Tishreen University. The researcher relied on the deductive approach as a method for thinking in formulating the research hypotheses and selecting the hypothesized relationships between the research variables, and the descriptive and analytical approach by listing Arab and foreign books and periodicals, and other publications related to the research topic, and reviewing, studying and analyzing them in order to answer the research objectives and discuss their hypotheses. As for the research methods, the researcher relied on the questionnaire as a tool for collecting primary data, and the questionnaire was distributed to a sample of 167 workers at Tishreen University, of which 164 were recovered, and 161 questionnaires were suitable for analysis. Then she analyzed the data on the dependent variable and the independent variable and tested the hypotheses using the analysis program. Statistician SPSS version 20 to accept or reject hypotheses. One of the most important results of the study was the content of the training program that is not commensurate with the needs of workers at work, and the training content is not determined on the basis of compatibility with the different abilities of the trainees, and the worker does not participate in choosing the appropriate work method and style, and the workers do not feel bored and bored because of my work.